Age of donor of human mesenchymal stem cells affects structural and functional recovery after cell therapy following ischaemic stroke. Issue 7 (July 2018) - Yamaguchi, Susumu; Horie, Nobutaka; Satoh, Katsuya; Ishikawa, Takeshi; Mori, Tsuyoshi; Maeda, Hajime; Fukuda, Yuhtaka; Ishizaka, Shunsuke; Hiu, Takeshi; Morofuji, Yoichi; Izumo, Tsuyoshi; Nishida, Noriyuki; et al.
Cell transplantation therapy offers great potential to improve impairments after stroke. However, the importance of donor age on therapeutic efficacy is unclear. We investigated the regenerative capacity of transplanted cells focusing on donor age (young vs. old) for ischaemic stroke. The quantities of human mesenchymal stem cell (hMSC) secreted brain-derived neurotrophic factor in vitro and of monocyte chemotactic protein-1 at day 7 in vivo were both significantly higher for young hMSC compared with old hMSC. Male Sprague-Dawley rats subjected to transient middle cerebral artery occlusion that received young hMSC (trans-arterially at 24 h after stroke) showed better behavioural recovery with prevention of brain atrophy compared with rats that received old hMSC. Histological analysis of the peri-infarct cortex showed that rats treated with young hMSC had significantly fewer microglia and more vessels covered with pericytes. Interestingly, migration of neural stem/progenitor cells expressing Musashi-1 positively correlated with astrocyte process alignment, which was more pronounced for young hMSC. Aging of hMSC may be a critical factor that affects cell therapy outcomes, and transplantation of young hMSC appears to provide better functional recovery through anti-inflammatory effects, vessel maturation, and neurogenesis potentially by the dominance of trophic factor secretion.